PENGGUNAAN EKSTRAK TEH DAN PUPUK KASCING PADA BUDIDAYA CAISIM (Brassica juncea L.) - Djoko Purnomo; Amalia T Sakya; Fuat Fahrudin (Faculty of Agriculture, Universitas Sebelas Maret, 2009)
Title : Using Tea Extract and Vermicompost on Caisim (Brassica juncea L.) Cultivation. The aim of the research is to know the effect of tea extract and vermicompost on yield and growth of caisim (Brassica juncea L.). The research was conducted in February-March 2009 in Screen House in Agriculture Faculty Sebelas Maret University at 96 meter above sea level. The research was arranged on factorial design based on Complete Randomize Design. The treatment of the research was tea extract with concentration 0, 10, 20, and 30 g/L and dosage vermicompost 0, 4, 8 and 12 ton/acre (equal 0, 10, 20 and 30 g/crop). Each treatment was repeated 3 times, and each of them restating 2 crop unit. Data was analysized by analysis of variants with test of 0.05, if there was significant continued with test of Duncan 0.05. Research variable were plant height, leaf number, fresh and shoot biomass weight, fresh and biomass root weight, root volume, chlorophyll content, leaf area and root shoot ratio. Result of research show there is interaction between tea extract and vermicompost on shoot root ratio. Shoot root ratio increase by increasing tea extract concentration on caisim without vermicompost and with vermicompost 8 ton/acre. Application tea extract do not give significantly effect on growth and yield of caisim. Dose vermicompost 8 ton/acre gave the highest of average fresh weight and leaf number. Keywords: caisim, tea extract, vermicompost